Adsorption Isotherm Studies on Acid Orange-10 Dye Removal using Cerium Dioxide Nanoparticles - Harry Budiman; Oman Zuas (Indonesian Journal of Chemistry, 2014)
The adsorption capacity of AO-10 from aqueous solution onto CeO2-NPs was investigated under various reaction parameters. Batch mode experiments were conducted to assess the potential of the CeO2-NPs as adsorbent for the removal of AO-10 dye from aqueous solution. Equilibrium isotherm studies were carried out under an optimum reaction condition (i.e., AO-10 dye concentration = 15 mg/L, CeO2-NPS dosage = 2 g/L, pH of dye solution = 2) obtained from this study. The equilibrium data obtained were fitted to Langmuir, Freundlich, and Redlich-Peterson isotherm models. The results shows that, the linear transform model provided the highest regression coefficient (R2 = 0.991) with the Langmuir model. The maximum monolayer adsorption capacity was found to be 33.33 mg/g at 30 °C, which is higher than some data from published literature.